Uncertainty, macroprudential policies and corporate leverage: Firm-level evidence - Ibrahim Yarba; Z. Nuray Güner (Central Bank Review (CBR), 2020)
This paper investigates the impact of macroprudential policies and uncertainty of economic environment on corporate leverage dynamics over the last decade. This is the first study to investigate the impact of macroprudential policies and uncertainty on leverage dynamics of Turkish non-financial firms using firm-level data. We argue in this paper that persistence of uncertainty should be a more appropriate factor affecting credit dynamics rather than uncertainty. In that sense, we construct a measure of uncertainty by using principal component analysis and a measure of persistence of uncertainty for Turkey. Results from the dynamic panel models with a large set of control variables, provide significant evidence in support of the argument that leverage decisions are affected from the persistence of uncertainty rather than the uncertainty itself. Moreover, both the share of the financial debt in total liabilities and the leverage of Turkish non-financial firms decrease significantly when uncertainty increases persistently and when macroprudential policy tools are tightened. Most strikingly, this is the case only for Small and Medium-Sized Enterprises but not for large firms.
Keywords: C23; D22; D81; G18; G32; 330; Macroprudential policy; Uncertainty; Persistence of uncertainty; Firm financial debt